2018
DOI: 10.1007/s00216-018-1427-6
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric absorptive microsampling as an alternative sampling strategy for the determination of paracetamol in blood and cerebrospinal fluid

Abstract: In the field of bioanalysis, dried matrix spot sampling is increasingly receiving interest, as this alternative sampling strategy offers many potential benefits over traditional sampling, including matrix volume sparing properties. By using a microsampling strategy, e.g. volumetric absorptive microsampling (VAMS), the number of samples that can be collected from a patient can be increased, as a result of the limited sample volume that is required per sample. To date, no VAMS-based methods have been developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…More likely, these results could be explained by a decreased and/or more variable efficiency of the wash procedure, leading to an increased presence of APAP-Cys free in the samples after the wash procedure, resulting in a notable increase in the measured concentrations in these samples. Previous reports in literature have indicated that the extraction of small molecules from VAMS samples can be dependent on the storage condition, which is in support of this theory (Delahaye et al, 2019;Xie et al, 2018). On the other hand, the results obtained for the stability of the blood VAMS samples after storage at 50 °C are all below or approximate the lower limit of acceptance.…”
Section: No Carry-over Was Observed Upon Injection Of Blank Samples After the Uloq Calibrator Samples (N=3x2)supporting
confidence: 71%
See 1 more Smart Citation
“…More likely, these results could be explained by a decreased and/or more variable efficiency of the wash procedure, leading to an increased presence of APAP-Cys free in the samples after the wash procedure, resulting in a notable increase in the measured concentrations in these samples. Previous reports in literature have indicated that the extraction of small molecules from VAMS samples can be dependent on the storage condition, which is in support of this theory (Delahaye et al, 2019;Xie et al, 2018). On the other hand, the results obtained for the stability of the blood VAMS samples after storage at 50 °C are all below or approximate the lower limit of acceptance.…”
Section: No Carry-over Was Observed Upon Injection Of Blank Samples After the Uloq Calibrator Samples (N=3x2)supporting
confidence: 71%
“…As we aimed at setting up a procedure for the combined determination of APAP and APAPprotein adducts, the sample preparation for the quantitation of APAP precedes the wash and digestion steps described above (Delahaye et al, 2019). In short, the VAMS sample tips are removed from the handle and extracted in a 2 mL LoBind cup with 300 µL extraction solvent (methanol/water/FA -80/20/0.01), of which 250 µL is diluted with water (0.01% FA) to a total volume of 1.0 mL and injected onto the LC-MS/MS.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This is still within the Table 1 Results of within-and between-day accuracy (%bias) and precision (%RSD) for QC blood VAMS samples prepared at LLOQ (0.4 µg/mL), low (2.0 µg/mL), medium (20 µg/mL) and high (200 µg/mL) iohexol concentration level. predefined − 15-15% interval, however this can be a possible sign of degradation or a storage-induced recovery issue [52]. In the study of Salvador et al, iohexol DBS were stable at room temperature up to 9 months [24].…”
Section: Methods Validationmentioning
confidence: 99%
“…A difference between the fresh and the stored samples, on the other hand, might be due both to a time-dependent extraction efficiency issue and to actual instability of the target analyte. 68 However, if this difference is not observed at all HT levels, it is unlikely that analyte instability is the culprit. If the difference is observed at all HT levels, it may be worthwhile to repeat the experiment at a lower storage temperature, as this may indicate analyte instability.…”
Section: A C C E P T E Dmentioning
confidence: 99%